1
$\begingroup$

It is asked to solve the PDE

$$u_x + u_y + u = e^{x+2y}$$

My attempt: We have that $$\frac{dx}{1}=\frac{dy}{1}=\frac{du}{e^{x+2y}-u} $$

$\Rightarrow \frac{dy}{dx}=1 \Rightarrow y=x+C_1 \iff C_1=y-x$

$\Rightarrow \frac{du}{dx}= e^{x+2y}-u \iff \dot{u}+u=e^{x+2y} \iff \\ \frac{d}{dx}(e^x u) = e^{2x+2y} \iff u = e^{-x} ( \frac{1}{2}e^{2x+2y} + C_2)$

As $u$ is constant along its characteristics:

$$u(x,y)=\frac{e^{-x}}{2}(e^{2x+2y} + 2C_2(y-x))$$

where $C_2$ is any function of one variable. But wolfram gave the following answer

$$u(x,y)=\frac{e^{-x}}{4}(e^{2x+2y} + 4C_2(y-x))$$

as you can check here

What am I doing wrong?

$\endgroup$
3
$\begingroup$

You write $$ \frac{d}{dx}(e^xu)=e^{2x+2y} $$ and then integrate with respect to $x$. If you first replace $y$ by $x+C_1$ in the right-hand side, and then integrate, you integrate $$ e^{4x+2C_1} $$ which indeed gives a division by $4$. The constant in front of $C_2$ does not matter, since $C_2$ is arbitrary.

$\endgroup$
2
$\begingroup$

The first passage already seems wrong to me: $$\frac{dx}{1}=\frac{du}{e^{x+2y}-u}\iff u_x= e^{x+2y}-u$$ so where is $u_y$?

In fact if you add it to the other one, which is $$\frac{dy}{1}=\frac{du}{e^{x+2y}-u}\iff u_y= e^{x+2y}-u$$ you get the wrong relation $u_x+u_y+2u=2e^{x+2y}$, which is probably where the factor $2$ comes from.

$\endgroup$
  • $\begingroup$ The $u$ in these equations is $u(s,s+c)$ which can also be written as $u(x,x+c)$ so that $\frac{d}{dx}u(x,x+c)=u_x+u_y=e^{x+2y}-u$. $\endgroup$ – Dr. Lutz Lehmann Feb 2 '18 at 8:06

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.